1925
DOI: 10.1002/recl.19250440313
|View full text |Cite
|
Sign up to set email alerts
|

Nitrierung mit Nitraten. II

Abstract: 141 (1925).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, a reasonable assumption is that the nitrating mixture converts the added chloride to an active chlorinating agent (or agents). Menke originally suggested that the intermediate formed during the eponymous reaction is the nitrating agent acetyl nitrate, and this postulate has been accepted elsewhere . Furthermore, it has been shown that the closely related nitrating reagent benzoyl nitrate reacts with chloride ions to form nitryl chloride and/or chlorine, both of which are effective chlorinating agents of aromatic systems such as toluene .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a reasonable assumption is that the nitrating mixture converts the added chloride to an active chlorinating agent (or agents). Menke originally suggested that the intermediate formed during the eponymous reaction is the nitrating agent acetyl nitrate, and this postulate has been accepted elsewhere . Furthermore, it has been shown that the closely related nitrating reagent benzoyl nitrate reacts with chloride ions to form nitryl chloride and/or chlorine, both of which are effective chlorinating agents of aromatic systems such as toluene .…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic nitrations are routine reactions in organic chemistry. However, the only reported example in metallabenzene chemistry is mononitration of the neutral osmabenzene OsI­(C 5 H 4 {SMe-1})­(CO)­(PPh 3 ) 2 using “Menke conditions” (i.e., copper nitrate and acetic anhydride at 0 °C) to give OsI­(C 5 H 3 {SMe-1}­{NO 2 -4})­(CO)­(PPh 3 ) 2 in very low (5%) yield. Substitution occurs at the C4 position, para to the SMe substituent, following conventional substituent directing effects .…”
Section: Introductionmentioning
confidence: 99%
“…Thiophanate-methyI-/>/¡ercy/-14C(I/). Among many reports on the nitration of aniline, the method of Menke (1925) was adopted because it appeared to give the highest ortho substitution (70.6 %). In this reaction it was found to be necessary to dry cupric nitrate thoroughly before use and to chill the reaction mixture enough while the granules of cupric nitrate were being crushed with a glass rod.…”
Section: Methodsmentioning
confidence: 99%
“…Our quick entry into these systems commenced with the mononitration of p h e n~l -U -~~C or -U-14C by the Cu(N03)2/HOAc reagent of Menke [ 7 ] . Contrary to this report of exclusive ortho nitration, we consistently obtained a mixture of 0-and p-nitrophenol (1 and 5) in a ratio of 1:2 to 2 : 3 , which was not significantly affected by lowering reaction temperatures below 25'C.…”
Section: I3c Of 84%mentioning
confidence: 99%